Review on Fractal Analysis of Porous Metal Materials - J. Z. Wang; J. Ma; Q. B. Ao; H. Zhi; H. P. Tang (Journal of Chemistry)
Porous metal materials are multifunctional lightweight materials and have been used widely in industry. The structural and functional characters of porous metal materials depend on the pore structure which can be described effectively by the fractal theory. This paper reviews the major achievements on fractal analysis of pore structure of porous metal materials made by State Key Laboratory of Porous Metal Materials, China, over the past few years. These include (i) designing and developing a set of novel fractal analytical software of porous metal materials, (ii) the influence of material characterization and image processing method on the fractal dimension, and (iii) the relationship between the material performance and the fractal dimension. Finally, the outlooks of fractal theory applied in porous metal materials are discussed.